The Sustainability Concept of Osing Traditional House in Kemiren Banyuwangi - Cayarini, Filomina Dwi; Titisari, Ema Yunita; Wikantiyoso, Respati (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
Nowadays, the high development of technologies and the density of the population demands high housing necessity. If there is no balanced between them and the environmentally concept, it will certainly cause problems to the next generation in the future. The sustainability concept in architecture is one alternative way which can be used to overcome this problem. Based on the prior theory, the traditional house applies the concept of sustainable architecture. Osing Traditional House from Osing Tribe also uses the concept. The Osing traditional house is located in Banyuwangi City. This study aims to prove the truth of the theory of sustainable architecture concept in traditional houses, especially in the Osing Traditional Houses in Banyuwangi and identify spatial patterns, structures, materials and other parameters that are considered to sustainable aspects. In the study, it was found that the Osing Traditional House includes aspects of topography, spatial patterns, structures and building materials as well as other parameters that contain to sustainable aspects. Keywords:     Sustainable Architecture, Osing Traditional House, Sustainable Aspects